Team PUCRS: a decentralised multi-agent solution for the agents in the city scenario. (2018) - Cardoso, Rafael C.; Pereira, Ramon Fraga; Krzisch, Guilherme; Magnaguagno, Maurício C.; Baségio, Túlio; Meneguzzi, Felipe
The 2016 edition of the multi-agent programming contest used the agents in the city as its new scenario, which consisted on the execution of various logistics tasks within a realistic city topology using a number of different vehicle types. The complexity of the scenario and variety of tasks posed a challenging problem suitable for a decentralised multi-agent solution. In this paper we describe the winning solution for the contest, providing insights into how we designed our solution and organised our team, as well as some discussion on a few of our matches.